Keterbatasan Finansial Keluarga Yang Berdampak Kepada Pendidikan Anak - Ani Qotuz Zuhro' Fitriana; Shahreza Shahmanda; Lailatus Salamah (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study examines the impact of financial limitations within a family on children's education, focusing on the dynamics of a family with four children at various educational stages and individual dependents. The constrained economic condition creates internal conflicts, where the children experience uncertainty in choosing between continuing their education or working to alleviate their parents' financial burden. Nevertheless, these limitations also bring positive aspects, such as strengthening character, responsibility, and family solidarity. This research employs a qualitative approach using a case study method to explore the family's experiences in facing these challenges. The results indicate the need for support from various parties to ensure the continuity of children's education and prevent school dropouts due to economic problems. Accordingly, this study offers strategic solution recommendations to assist underprivileged families in fulfilling their children's right to education.